Characteristics Physicals and Chemicals of Probiotic Drinks Soy-Yamghurt - Nurhasanah; Rusmarilin, Herla; Silalahi, Jansen (Indonesian Journal of Agricultural Research, 2022)
Soy-yamghurt is fermentation product of yam-bean extract and soybean extract made by adding bacterium Lactobacillus bulgaricus, Lactobacillus acidophilus and Streptococcus thermophillus which are commonly used in the process of making yoghurt. This study aims to determine the physical and chemical characteristics of soy-yamghurt probiotic drinks. The research used a completely randomized design factorial with two factors, i.e.: ratio of yam-bean extract with soybean extract (100%:0%; 75%:25%; 50%:50%; 25%:75%; 0%:100%) and fermentation periods (4 hours; 6 hours; 8 hours). The result showed that ratio of yam-bean extract with soybean extract had highly significant effect on color test value, viscosity, moisture content, protein content, total sugar content, reducing sugar content, starch content, and glucose content. In the meantime, the fermentation periods had highly significant effect on viscosity, moisture content, total sugar content, reducing sugar content, starch content, glucose content and had significant effect on color and protein content. Interaction between the two factors had a highly significant effect on viscosity, reducing sugar content and had significant effect on moisture content. Furthermore, the interaction had no significant effect on color, protein content, total sugar content, starch content, and glucose content. The best soy-yamghurt was produced with ratio of yam-bean with soybean extract 50:50 fermented for 6 hours.